PEMETAAN ANALISIS PERBANDINGAN TINGKAT KEBISINGAN DAN VOLUME KENDARAAN PADA RUAS JL. PANDE REJO, LEGOK - JL. SOEKARNO HATTA PASURUAN KOTA - Abdullah Ubaid Hartawan; Hendrata Wibisana; Siti Zainab (LPPM Universitas Abdurrab, 2025)
Pasuruan Regency provides an access road from Surabaya to Banyuwangi and Bali. The access from Surabaya to Banyuwangi and Bali is one of the roads with quite heavy traffic. In the future, of course, traffic volume will continue to become increasingly dense. Apart from that, Pasuruan Regency also has an alternative route that can quickly connect motorists to Pandaan, Sukorejo and Malang. Due to these factors, the potential for sound or noise pollution along roads in Pasuruan Regency is something that needs attention. The aim of this research is to examine the relationship between vehicle volume and noise due to the influence of traffic and to determine a map of the distribution of noise levels along JL Raya Pande Rejo, Legok to Jl. Soekarno Hatta Pasuruan city. This research uses Geographic Information System tools to display thematic maps. In order to get better results, this should be done during peak hours, namely 07.00 - 09.00 in the morning and 16.00 - 18.00 in the afternoon. From the noise level calculation, it was found that the highest noise in the morning was on Jalan Attorney General Suprapto (Segment 4) with a noise value of 81.74 (dBA) caused by the dense traffic volume on Jalan Attorney General Suprapto (Segment 4) of 2040.9 junior high school/hour. So the noise produced is also very large. The results of calculations using the multiple linear regression method, obtained an R2 value of 0.938 on Jalan Attorney General Suprapto with a fairly strong positive correlation value of 0.796 for MC vehicles. It can be concluded that a positive correlation means that the more vehicle volume, the higher the noise level received.